Drosophila Topoisomerase 3β binds to mRNAs in vivo, contributes to their localization and stability, and counteracts premature aging. - Shohreh Teimuri; Beat Suter (PLoS ONE)
Topoisomerase 3β (Top3β) works not only on DNA but also on RNA. We isolated and identified the naturally cross-linked RNA targets of Drosophila Top3β from an early embryonic stage that contains almost exclusively maternal mRNAs. Favorite targets were long RNAs, particularly with long 3'UTRs, and RNAs that become localized in large cells. Top3β lacking only the hydroxyl group that makes the covalent bond to the RNA, did not allow normal expression and localization of Top3β mRNA targets or their protein products, demonstrating the importance of the enzymatic activity of Top3 β for optimized gene expression. Top3β is not essential for development to the adult stage but to maintain the morphology of the adult neuromuscular junction and to prevent premature loss of coordinated movement and aging. Alterations in human Top3β have been associated with several neurological diseases and cancers. The homologs of genes and (pre)mRNAs mis-expressed in these conditions show the same characteristics identified in the Drosophila Top3β targets, suggesting that Drosophila could model human Top3β. An in vivo test of this model showed that the enzymatic activity of Top3β reduces the neurodegeneration caused by the cytotoxic human (G4C2)49 RNA. Top3β supports normal gene expression, particularly of long and complex transcripts that must be transported and translationally controlled. These RNAs encode large cytoskeletal, cortical, and membrane proteins that are particularly important in large and long cells like motoneurons. Their reduced expression in the mutant seems to stress the cells, increasing the chances of developing neurodegenerative diseases.